Beyond alpha-band: The neural correlate of creative thinking. (28th January 2023) - Mazza, Alessandro; Dal Monte, Olga; Schintu, Selene; Colombo, Samuele; Michielli, Nicola; Sarasso, Pietro; Törlind, Peter; Cantamessa, Marco; Montagna, Francesca; Ricci, Raffaella
Abstract: The compound nature of creativity entails the interplay of multiple cognitive processes, making it difficult to attribute creativity to a single neural signature. Divergent thinking paradigms, widely adopted to investigate creative production, have highlighted the key role of specific mental operations subserving creativity, such as inhibition of external stimuli, loose semantic associations, and mental imagery. Neurophysiological studies have typically shown a high alpha rhythm synchronization when individuals are engaged in creative ideation. Also, oculomotor activity and pupil diameter have been proposed as useful indicators of mental operations involved in such a thinking process. The goal of this study was to investigate whether beyond alpha-band activity other higher frequency bands, such as beta and gamma, may subserve divergent and convergent thinking and whether those could be associated with a different gaze bias and pupil response during ideas generation. Implementing a within-subjects design we collected behavioral measures, neural activity, gaze patterns, and pupil dilation while participants performed a revised version of the Alternative Uses Task, in which divergent thinking is contrasted to convergent thinking . As expected, participants took longer to generate creative ideas as compared to common ones. Interestingly, during divergent thinking participants displayed alpha synchronization along with beta and gamma desynchronization, more pronounced leftward gaze shift, and greater pupil dilation. During convergent thinking, an opposite pattern was observed: desynchronization in alpha and an increase in beta and gamma rhythm, along with a reduction of leftward gaze shift and greater pupil constriction. The present study uncovered specific neural dynamics and physiological patterns during idea generation, providing novel insight into the complex physiological signature of creative production. Highlights: Creativity entails Divergent thinking (DT) and Convergent thinking (CT) processes. DT is linked to alpha synchronization and beta and gamma desynchronization. CT is characterized by alpha desynchronization and beta and gamma synchronization. DT is also coupled with leftward gaze shift and greater pupil dilation. Different neurophysiological patterns underpin creative idea generation.